2012
DOI: 10.1155/2012/438912
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antinociceptive Effects of Salbutamol on Acute and Chronic Models of Inflammation in Rats: Involvement of an Antioxidant Mechanism

Abstract: The possible role ofβ-2 adrenergic receptors in modulation of inflammatory and nociceptive conditions suggests that theβ-2 adrenergic receptor agonist, salbutamol, may have beneficial anti-inflammatory and analgesic effects. Therefore, in this study, we induced inflammatory and nociceptive responses with carrageenan-induced paw edema or cotton-pellet-induced granuloma models, both of which result in oxidative stress. We hypothesized that salbutamol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 71 publications
8
41
0
Order By: Relevance
“…SOD and GSH are the main components involved in the antioxidative system and limit the cytotoxic effects of toxic free radicals (Fink, 2002). Many inflammation studies have demonstrated reduced antioxidant levels in paw tissues (Halici et al, 2007;Uzkeser et al, 2012). In the present study, AS-19 increased antioxidant enzyme activity in paws, which had been significantly decreased by carrageenan induced inflammation.…”
Section: Discussionsupporting
confidence: 50%
“…SOD and GSH are the main components involved in the antioxidative system and limit the cytotoxic effects of toxic free radicals (Fink, 2002). Many inflammation studies have demonstrated reduced antioxidant levels in paw tissues (Halici et al, 2007;Uzkeser et al, 2012). In the present study, AS-19 increased antioxidant enzyme activity in paws, which had been significantly decreased by carrageenan induced inflammation.…”
Section: Discussionsupporting
confidence: 50%
“…The granuloma is characterized by the formation of a fibrous vascularized capsule containing fibroblast and mononuclear infiltrate cells. Decreased granuloma tissue formation, prevention of occurrence of the collagen fibres and suppression of mucopolysaccharides are indicators of the anti-proliferative effect of NSAIDs (41). Daily topical application of the microemulsion formulations TNX 03 and TNX 04 significantly (p<0.001) inhibited granulomatous tissue formation, in comparison to TNX 01, TNX 02 and control (Fig.…”
Section: Cotton Pellet Granuloma In Ratsmentioning
confidence: 86%
“…This study was aimed at evaluating the anti-inflammatory effect 37 of riparin A against acute inflammation. The results of our evaluations in various experimental models 38 indicated that riparin A reduced paw edema induced by carrageenan, compound 48/80, histamine, and 39 serotonin. Furthermore, it decreased leukocyte and neutrophil counts, myeloperoxidase activity, thiobar- 40 bituric acid reactive substance (TBARS) levels, and cytokine (tumor necrosis factor-a and interleukin-1b) 41 levels increased by carrageenan-induced peritonitis, and reversed glutathione levels.…”
mentioning
confidence: 78%